Penerapan Model Kooperatif Tipe TGT Untuk Meningkatkan Motivasi Belajar Siswa Pada Materi Denah Kelas III SD Muhammadiyah I Purworejo - Annisa Rahmi Restyani; Herlina Setyowati; Titi Anjarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research aimed to describe the implementation of the Teams Games Tournament (TGT) cooperative learning model and analyze the improvement of students’ learning motivation in Social Science content within IPAS on map-reading material. The study involved 20 third-grade students of SD Muhammadiyah I Purworejo and was conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through observation, questionnaires, interviews, tests, documentation, and field notes. The results showed that the TGT model improved students’ learning motivation. Observation results increased from 29.05% in the pre-cycle to 52.08% in Cycle I and 86.67% in Cycle II. Questionnaire results increased from 48.84% to 64.25% and 83.81%. Learning implementation also increased from 74.29% to 95.71%. Therefore, the TGT model effectively improved students’ learning motivation and learning outcomes.